1989
DOI: 10.1016/0741-5214(89)90342-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and results of arterial complications among 16,350 patients undergoing cardiac catheterization

Abstract: A total of 16,350 patients underwent cardiac catheterization from January 1981 to December 1987. The brachial artery was used in 10,500 patients (group I), and the femoral artery was used in 5850 patients (group II). Surgical intervention for complications was necessary in 60 (0.57%) of the group I patients and in 14 (0.23%) of the group II patients. Hand ischemia in group I and bleeding in group II were the most frequent indications for operation. Procedures performed were segmental resection, vein interposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
6

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(40 citation statements)
references
References 11 publications
2
32
0
6
Order By: Relevance
“…These observations may be supported by the Babu et al study, which showed that the brachial approach has a greater complication rate than the femoral approach: that is, surgical intervention for complications was necessary in 60 (0.57%) of brachial approach patients and in 14 (0.23%) of femoral approach patients. 24 In contrast, at Kokura Memorial Hospital, the incidence of brachial PSA was lower than that of femoral PSA. This may be because the incidence of PSA is possibly influenced by the difference in hemostatic methods used after removing the sheath, for example, manual compression of the femoral artery vs. a Tometa-Kun TM compression device 25 in the brachial artery.…”
Section: Discussionmentioning
confidence: 76%
“…These observations may be supported by the Babu et al study, which showed that the brachial approach has a greater complication rate than the femoral approach: that is, surgical intervention for complications was necessary in 60 (0.57%) of brachial approach patients and in 14 (0.23%) of femoral approach patients. 24 In contrast, at Kokura Memorial Hospital, the incidence of brachial PSA was lower than that of femoral PSA. This may be because the incidence of PSA is possibly influenced by the difference in hemostatic methods used after removing the sheath, for example, manual compression of the femoral artery vs. a Tometa-Kun TM compression device 25 in the brachial artery.…”
Section: Discussionmentioning
confidence: 76%
“…The Angio-Seal device consists of (1) a delivery device composed of a biodegradable anchor and a collagen plug; (2) an insertion sheath and arteriotomy locator, which is a modified dilator; and (3) a 0.035-or 0.038-inch 70-cm J-tip guidewire. A femoral angiogram should be obtained before the procedure to ensure that there are no contraindications (as discussed above).…”
Section: Angio-seal Insertion Techniquementioning
confidence: 99%
“…1 It is an often underestimated but important aspect of the procedure, and is the single most frequent cause of complications during coronary angiography and intervention. 2 Hyperlinked to this article is a video that shows a PVI procedure performed at VA Boston Healthcare System, West Roxbury Campus. Most vascular complications are preventable by following good access technique, starting with a thorough history and physical examination.…”
mentioning
confidence: 99%
“…We have found that thrombosis with obliteration of the pseudoaneurysm can be carried out successfully in patients who are fully anticoagulated. Thrombus formation in the hematoma may occur despite anticoagulation owing to two factors; (1) lack of endothelial surface, and (2) blockade of fresh arterial inflow. The complete thrombosis of the pseudoaneurysmcavity promotes stability of the platelet.…”
Section: Discussionmentioning
confidence: 99%